The Influence Of MSMES On Economic Growth - Akbarina, Farida; Ariani, Dian; Rijal, Syamsu (Journal of Management, 2024)
This type of research is descriptive qualitative and uses literary analysis; The aim of this research is to provide assessment material to stakeholders in the company's efforts to achieve optimal national economic results. The author of this research used a literature study taken from Publish & Perish as a data collection technique. Publish & Perish also uses analytical techniques to collect previous research. This research shows that business ethics plays an important role in shaping the economic activities of businesses, societies, and governments. The dynamics of this business activity can improve the economy and the general public's sense of well-being. Efforts to increase the number of entrepreneurs in Indonesia must continue to be made considering that the number of entrepreneurs is relatively small compared to the population. The facts show that improving the standard of living for individuals, communities and countries is a top priority for business owners. Entrepreneurship is also very important to produce a more cohesive society and nation.